Exploring responsible tourism management in tour operators - Patakorn Kaewmorakot; Nontipak Pianroj; Prachyakorn Chaiyakot (Songklanakarin Journal of Science and Technology (SJST))
Tour operators play a key role in advancing sustainable tourism, particularly with the growing emphasis on responsible tourism. However, documentation on their implementation of responsible tourism practices is limited. Variations between countries due to regional disparities and tourism types underscore the necessity for comprehensive research. This study aims to conduct a systematic literature review on global responsible tourism management by tour operators. This research establishes a connection between environmental responsibility practices or social responsibility and community engagement, and the 2022 Responsible Tourism Charter. The study identifies critical practices for urgent adoption by tour operators. Key environmental responsibility practices include resource efficiency measures, climate change mitigation and conservation efforts, and waste management and recycling. Social responsibility and community engagement practices are categorized into employee welfare and fair practices, community empowerment and collaboration, transparency and ethical practices, community development and awareness, and inclusive tourism and customer service.